Changing the Face of the Waters : The Promise and Challenge of Sustainable Aquaculture - World Bank (Washington, DC: World Bank, 2012)
This study provides strategic orientations and recommendations for Bank client countries and suggests approaches for the Bank's role in a rapidly changing industry with high economic potential. It identifies priorities and options for policy adjustments, catalytic investments, and entry points for the Bank and other investors to foster environmentally friendly, wealth-creating, and sustainable aquaculture. The objectives of the study are to inform and provide guidance on sustainable aquaculture to decision makers in the international development community and in client countries of international finance institutions. The study focuses on several critical issues and challenges: 1) Harnessing the contribution of aquaculture to economic development, including poverty alleviation and wealth creation, to employment and to food security and trade, particularly for least developed countries (LDCs); 2) Building environmentally sustainable aquaculture, including the role of aquaculture in the broader suite of environmental management measures; 3) Creating the enabling conditions for sustainable aquaculture, including the governance, policy, and regulatory frameworks, and identifying the roles of the public and private sectors; and 4) Developing and transferring human and institutional capacity in governance, technologies, and business models with special reference to the application of lessons from Asia to Sub-Saharan Africa and Latin America.